Retrospective Study on transfusion requirements and deep vein thrombosis incidence with the use of Tranexamic acid on total knee replacement - Rana, R; Lakhey, S; Jha, D; Chitrakar, N; Thakur, J; Poudel, A (Nepal Mediciti Medical Journal, 2022)
BACKGROUND Total knee replacement is often associated with significant blood loss and increased rate of blood transfusion. Tranexamic acid is a potent anti-fibrinolytic agent and its use in major surgeries has shown to decrease blood loss as well as transfusion rates. It is used intravenous, oral and topical forms as well. This study aims to find out the effectiveness of systemic Tranexamic acid in terms of decrease in transfusion rate as well incidence of deep vein thrombosis (DVT) and thromboembolism. MATERIALS AND METHODS Total number of patients were 94 of which 58 had bilateral knees replacement and 36 patient underwent unilateral knee replacement over the period of 3 years (December 2018 –December 2021). All patients were screened for general condition as well as any coagulopathy pre –op. All patients were given IV form of Tranexamic acid followed by oral form for 3 days post operatively. Tourniquet was used in all cases and low molecular weight heparin (Clexane) 40 mg subcutaneous once a day for 1-2 days followed by oral aspirin was given for 6 weeks to all patients. SCD calf pumps were used for 4 to 5 days. RESULTS We found that incidence of blood transfusion was only 6.9% in our case series which was well within the incidence reported in varied literature on the use of Tranexamic acid in knee replacement surgery. There was no clinical feature of deep vein thrombosis / pulmonary embolism (DVT/PE) in any of our patients. CONCLUSION Use of Tranexamic acid is a safe and effective method for controlling blood loss and decreasing the transfusion rate after total knee replacement surgery. Its intravenous and oral forms are readily available and cost effective. Its use is not associated with DVT or PE.